ON THE DEVELOPMENT OF THE ALBANIAN INFORMAL ECONOMY - Majlinda BELLO; Frederik ÇUÇLLARI; Mirela CINI (Management & Marketing)
The purpose of the paper is to analyze the informal economy in Albania. The measurement of informal economy may be realized through direct and indirect methods. The collection of data about informal economic activities, the frequency and the volume of the underground activities present a challenge, because of the data limitations. Therefore, to measure it used more indirect methods. Albanian governments have always adopted a philosophy that aims to formalize the economy through legal and institutional improvements, reducing taxes, fighting corruption and tax evasion; improvement in revenue collection from customs and taxes in general, improving governance and increasing efficiency of public institutions. Albania is on the way of the integration in the EU. The integration perspective should be supported by concrete politics on the improvement of government functioning and decrease of the informal sector, so that the people think that their country is on the right way toward modernization and prosperity.